An Analysis Of Sarcasme Language Communication In The Film Jakarta Vs Everybody - Aktri Veni; Yessy Octavianna; Susanti Susanti (STABN RADEN WIJAYA WONOGIRI, 2024)
This research analyzes the use of sarcastic language in the film Jakarta vs Everybody (2016) by employing Jonathan Culpeper’s (2011) theory of impoliteness strategies. The study aims to identify the types of sarcasm used, examine their meanings, and determine the most dominant type appearing in the dialogues. This research applies a descriptive qualitative method, with the researcher as the primary instrument. Data were obtained from the film’s transcript by observing, identifying, and categorizing utterances containing sarcasm.The findings reveal three types of sarcasm used in the film: irony (26 data / 63.41%), mock politeness (13 data / 31.70%), and over-politeness (2 data / 4.87%). No instances of deadpan sarcasm (0%) were found. Irony occurs when the speaker delivers an utterance whose literal meaning is positive but whose intended meaning is negative; mock politeness involves the use of insincere politeness to ridicule; and over-politeness exaggerates courtesy to convey criticism or satire. The meanings of sarcasm identified in the film generally carry harsh, demeaning, and critical nuances, functioning as tools for social commentary, emotional expression, and conflict in character interactions.Based on the analysis, irony is the most dominant type of sarcasm, appearing in 63.41% of the sarcastic utterances. This dominance indicates that the film frequently employs irony as a narrative device to reflect urban Jakarta’s social tensions and to shape character dynamics